Implementing Circular Economy in Universities. Successful Practices at Politecnico di Torino (Italy) - Lombardi, Patrizia; Genta, Chiara; Colaleo, Valentina (Journal of Sustainability Perspectives, 2023)
The circular economy (CE) concept reported a growing interest as an operationalizing framework, able to support the implementation of sustainable production and consumption, resource use and waste prevention broader concepts. Even if CE is different from waste management, it has traditionally been associated with waste reduction, recycling improvement, and minimization of environmental impacts in cities and territories. Additionally, CE could be a driver for the achievement of multiple Sustainable Development Goals (SDGs). On the other side, universities are recognized as key actors in the transition towards sustainable development at the territorial level. Given the use of CE as a possible change paradigm to decouple economic growth from associated environmental impacts, this paper aims at highlighting some of the main successful practices put forwards by an Italian university, Politecnico di Torino, in implementing CE principles.Keyword: Circular Economy, University Sustainability, waste management